PEMANFAATAN LIMBAH DOMESTIK MENJADI PRODUK AGRIBISNIS KOKEDAMA SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT LOKAL - Pintakami, Lintar Brillian; Fibrianingtyas, Alia; A, Tatiek Koerniawati; Amalia, Rizka; Sulaiman, Moh. Adi; Hermawanto, Steven Gerrard Christoffel; Putri, Daniyah Nabila Riyanti (Yayasan Education and Social Center, 2024)
This article aims to reduce the environmental impact of non-domestic waste by exploring various recycling and repurposing methods. It focuses on utilizing non-domestic waste as a base material for making kokedama, a Japanese planting technique that combines art and sustainability. The non-domestic waste selected includes industrial by-products such as coconut husks, used paper, and wood. The methodology involves collecting non-domestic waste from local communities, processing it into kokedama planting media, and providing training to the community on kokedama techniques. This training program is designed to enhance technical skills and environmental awareness among participants while creating new economic opportunities through the production and sale of kokedama. Research findings indicate that the training not only reduces waste volume but also empowers community members with new skills and increases their potential income. Active participation in the kokedama production process helps improve economic and social well-being and strengthens the sense of ownership towards environmental sustainability efforts. The study concludes that utilizing non-domestic waste in kokedama not only reduces waste volume but also offers an innovative and sustainable alternative in urban agriculture practices and has the potential to raise awareness about recycling